Simultaneous determination of miconazole and hydrocortisone or mometasone using reversed phase liquid chromatography - El-Bagary, Ramzia Ismail; Elkady, Ehab Farouk; Tammam, Marwa Hosny; Elmaaty, Ayman Abo (European Journal of Chemistry, 2012)
Two simple, rapid and precise reversed phase liquid chromatographic methods have been developed and validated for the simultaneous determination of miconazole nitrate in two binary mixtures, with hydrocortisone acetate (Mixture 1) and mometasone furoate (Mixture 2). For the two mixtures, chromatographic separation was carried out on a C18 column. For mixture 1, a mobile phase consisting of 2.22 mM sodium dihydrogen phosphate (Triethylamine 0.2%):acetonitrile (45:55, v:v) at a flow rate of 0.9 mL/min was used at ambient temperature. Quantitative determination of miconazole and hydrocortisone was achieved with UV detection at 215 and 245 nm, respectively. Linearity, accuracy and precision were found to be acceptable over the concentration range of 30-80 μg/mL for miconazole and 4-80 μg/mL for hydrocotisone. For mixture 2, a mobile phase consisting of acetonitrile:water (Triethylamine 0.2%) (70:30, v:v) at a flow rate of 0.9 mL/min was used at ambient temperature. Quantitative determinations of miconazole and mometasone were achieved with UV detection at 215 and 250 nm, respectively. Linearity, accuracy and precision were found to be acceptable over the concentration range of 10-200 μg/mL for miconazole and 2-60 μg/mL for mometasone. The optimized methods were proved to be specific, robust and accurate for the quality control of the cited drugs in pharmaceutical preparations.